Development and Evaluation of an Integrated Nutritional Health Care Information System - Chen, Yuner; Li, Mu; Xie, Weijie; Feng, Xiuxia; Tian, Huishu; Wang, Wenhui (Applied Clinical Informatics, 2025)
Malnutrition remains a critical global health challenge among hospitalized patients, necessitating effective nutrition support systems.This study aims to construct and evaluate a cross-professional, cross-sectoral nutrition health care information system (CPCS-NHIS) to optimize clinical nutrition management.The system integrates modified medical systems to unify information flows, knowledge, and clinical roles. In addition, a 20-item across six dimensions electronic questionnaire based on the revised DeLone and McLean IS Success model was developed to evaluate the success of the CSCP-NHIS. Besides, user satisfaction was assessed as a key dimension using a 5-point Likert's scale (1 = strongly disagree to 5 = strongly agree). Finally, the results of the questionnaire were further validated by reliability and validity analysis.The CPCS-NHIS features comprehensive functions including bedside nutritional screening, assessment, intervention, diagnosis, monitoring, enteral nutrition prescription, and QR-code autopayment. Over 80% of users expressed willingness to continue using and recommending the system. The questionnaire results demonstrated strong psychometric properties: all Cronbach's α coefficients >0.80, confirmed reliability; confirmatory factor analysis showed convergent validity (the average variance extracted >0.50, construct reliability >0.80); and model fit indices were excellent, with a chi-square value of 1.86, a root mean squared error of approximation of 0.09, a root mean square residual of 0.02, and a comparative fit index of 0.9.The CPCS-NHIS provides a practical framework for existing nutritional health care information systems, based on the nutrition care process and model, with robust psychometric evidence and high user acceptance.
Keywords: nutritional health care information system; revised DeLone and McLean IS success model; reliability and validity; nutritional diagnosis and treatment; cross-professional and cross-sectoral model